Penjaringan Mahasiswa Baru Melalui Sosialisasi Akademik Jurusan Pembangunan Sosial Bagi Siswa SMA/SMK di Kabupaten Merauke - Oja, Hubertus; Saragih, Dapot Pardamean; Irawan, Andri; Purnama, Erwin Nugraha; Kontu, Fransin; Mardiana, Wa Ode Sitti; Lekatompessy, Ransta L. (UNIB Press, 2025)
This Social Development Study Program is one of the new study programs at Musamus Merauke University, more specifically at the Faculty of Social and Political Sciences. As a new study program, of course, not much is known by the people in the southern region of Papua about the existence of this study program, so with this socialization, at least it can provide important information for the community of the existence of this study program. This academic socialization activity is not only to introduce and provide academic information about the study program to the wider community, but also to attract new students so that this study program gets its own specialization, especially for students who want to advance their education at a higher level, so with this activity it can attract the interest of prospective students to choose and join this study program..